Multifunctional paper protection liquid based on nano GeO2 / CTAB (cetyltrimethyl ammonium bromide) compound and application of multifunctional paper protection liquid in paper protection

By using nano-GeO2/CTAB composite paper protective liquid, the problem of degradation of paper cellulose by microorganisms is solved, and the paper is reinforced, anti-mold and anti-ultraviolet effects are achieved, which extends the service life of the paper and restores its original luster and texture.

CN119531186APending Publication Date: 2025-02-28JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411701141.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent the degradation and destruction of paper cellulose by microorganisms, and commonly used antibiotics have toxic side effects on paper cellulose, which limits its application scope.

Method used

A paper protective liquid based on nano-GeO2/CTAB composite is used. By applying nanomaterials to the paper surface, the composite improves the appearance of the paper, enhances the support effect of cellulose, and has anti-mold, anti-bacterial and anti-ultraviolet rays.

Benefits of technology

This paper protective liquid can not only strengthen paper cellulose and prevent microbial invasion, but also effectively isolate ultraviolet radiation, extend the service life of the paper, and restore its original luster and texture when repairing paper cultural relics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119531186A_ABST
    Figure CN119531186A_ABST
Patent Text Reader

Abstract

The invention discloses a paper protection liquid based on a nano GeO2 / CTAB (cetyltrimethyl ammonium bromide) compound and application of the paper protection liquid in paper protection, and belongs to the technical field of paper protection. The protection liquid is obtained by dissolving a nano GeO2 / CTAB (cetyltrimethyl ammonium bromide) compound in deionized water, wherein the nano GeO2 / CTAB compound is formed by mixing germanium dioxide, NaOH and CTAB in a water phase according to a certain proportion and growing. The advantages of weather resistance and ultraviolet resistance of the nano GeO2 / CTAB compound are fully utilized, and paper repaired by the multifunctional protection liquid better embodies the principle of'repairing old as new 'of cultural relic protection in the aspects of gloss, texture and the like; the nano GeO2 / CTAB compound paper protection liquid not only can inhibit the growth and reproduction of gram-positive bacteria and gram-negative bacteria on the surface of paper, but also can play a good role in killing and inhibiting fungi and spores thereof separated from the surface of the paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of paper protection, and in particular relates to a paper protection liquid based on a nano-GeO2 / CTAB composite and application thereof in paper protection. Background Art

[0002] Paper damage has become a problem that all mankind has to face. Paper is a thin film material with cellulose and hemicellulose as the main components. The essence of paper damage is the damage and breakage of the cellulose that constitutes the paper. There are many factors that cause paper damage, among which microbial invasion, especially the degradation of paper cellulose by fungi, is one of the main factors of paper damage. Fungi can seriously degrade and destroy paper cellulose because fungi can not only secrete highly active degradation enzymes, but also survive in low-nutrient environments. At present, many different types of fungi have been isolated from paper, such as Penicillium, Aspergillus, Fusarium and Trichoderma. Most fungi in the environment can maintain their survival by producing different types of cellulases, which are the main culprits of paper cellulose degradation. In addition to cellulases, amylases, xylanases and gelatinases also play a key role in the degradation of paper components. As the fungi colonized on the paper grow and develop, the mechanical pressure exerted on the paper cellulose by the extracellular enzymes and hyphae produced will also make the paper more fragile. Since fungal metabolites and their derivatives contain acidic substances, these acidic substances that stay on the surface of the paper for a long time can also accelerate the breakage of the cellulose chain of the paper. Although commonly used antibiotics have significant antibacterial effects, they have different degrees of toxic side effects on paper cellulose and may accelerate the damage of paper, resulting in a certain limitation on their application scope. Therefore, it is of great practical significance to study a multifunctional paper protection liquid that integrates mildew and antibacterial, reinforcement, and UV resistance. Summary of the invention

[0003] In view of the above situation, in order to solve the problem of paper cellulose breakage caused by microorganisms, the present invention aims to provide a paper protection liquid based on nano-GeO2 / CTAB complex and its application in paper protection. The paper protection liquid based on nano-GeO2 / CTAB complex obtained by the present invention can not only strengthen the paper cellulose, but also make the paper have mildew and antibacterial properties, and fully utilize the weather resistance and UV resistance advantages of GeO2 / CTAB complex, and can effectively strengthen and isolate existing paper cultural relics from ultraviolet radiation. The present invention fully utilizes the weather resistance and UV resistance advantages of nano-GeO2 / CTAB complex, and the paper repaired by the multifunctional protection liquid better embodies the principle of "repairing the old as new" in cultural relic protection in terms of gloss and texture.

[0004] The invention provides a paper protection liquid based on nano-GeO2 / CTAB composite, which is obtained by dissolving the nano-GeO2 / CTAB composite in deionized water, wherein the concentration of the nano-GeO2 / CTAB composite is 0.1-5 mg / mL; wherein the nano-GeO2 / CTAB composite is formed by mixing and growing germanium dioxide, NaOH and CTAB in a certain proportion in an aqueous phase.

[0005] The paper protection liquid based on nano-GeO2 / CTAB composite described in the present invention is prepared by the following steps:

[0006] (1) First, add raw GeO2 (raw GeO2 refers to germanium dioxide purchased without any processing, which is here to make a clear distinction from the nano-GeO2 / CTAB composite synthesized later in the present invention) and NaOH into 10 mL of ultrapure water, so that the concentration of Raw GeO2 in the mixed solution is 0.9 M and the concentration of NaOH is 0.2-0.5 M, and stir at 25-30° C. for 10-15 h; then pour 12 mL of CTAB solution with a concentration of 0.1-0.5 M into the mixed solution and stir for 5-8 h; after the stirring is completed, heat the Raw GeO2 mixture at 90-110° C. for 48-72 h; after the reaction is completed, centrifuge at 8000-12000×g for 10-15 min and collect the reaction product, wash the reaction product with ultrapure water and anhydrous ethanol for 2-4 times respectively, and remove the impurities that have not reacted completely from the product; finally, vacuum dry at 50-60° C. to obtain the nano-GeO2 / CTAB composite;

[0007] Furthermore, the NaOH concentration is 0.3-0.5M, the stirring time of the mixed solution of Raw GeO2 and NaOH at 25-30°C is 12-15h, the CTAB solution concentration is 0.3-0.5M, the stirring time after adding the CTAB solution to the mixed solution of Raw GeO2 and NaOH is 6-8h, the Raw GeO2 mixture is heated and grown at 90-110°C for 56-72h, and the impurities that have not reacted completely are removed from the product by washing with ultrapure water and anhydrous ethanol for 2-4 times respectively, which is first washing with ultrapure water for 2-4 times and then washing with anhydrous ethanol for 2-4 times.

[0008] (2) Preparation of nano-GeO2 / CTAB complex protective solution: dissolving the nano-GeO2 / CTAB complex obtained in step (1) in deionized water to obtain a nano-GeO2 / CTAB complex protective solution with a concentration of 0.1 to 5 mg / mL; the preferred concentration is 1 to 5 mg / mL;

[0009] (3) Nano-GeO2 / CTAB composite protective liquid can be effectively used for paper reinforcement and protection. The method of use is: immerse the paper in the nano-GeO2 / CTAB composite protective liquid at 10-40°C for 5-30 minutes, then take it out and dry it at 20-40°C for 2-5 days;

[0010] The method comprises immersing the paper in a nano-GeO2 / CTAB composite protective liquid at 25-35°C for 5-10 minutes and then taking it out; the drying temperature after the paper is taken out is preferably 30-40°C, and the drying time is preferably 2-3 days.

[0011] The nano-GeO2 / CTAB composite protective liquid is used for reinforcing, inhibiting bacteria, and isolating ultraviolet radiation of paper cellulose; and is used for inhibiting one or more of Staphylococcus aureus, Escherichia coli, Aspergillus niger, Penicillium, Trichoderma, and Fusarium in paper.

[0012] The surfactant may be, in addition to cetyltrimethylammonium bromide (CTAB), bis(decyldimethylammonium chloride) or benzalkonium chloride.

[0013] Compared with the existing paper protection liquid, the present invention has the following characteristics:

[0014] 1) As a white nanomaterial, nano-GeO2 / CTAB composite can significantly improve the aging and yellowing problem of paper after being applied on the surface of paper;

[0015] 2) Use CTAB to adjust the morphology of the nano-GeO2 / CTAB composite and enhance its support and reinforcement effect on paper cellulose;

[0016] 3) Nano-GeO2 / CTAB complex has inhibitory effects on both Gram-positive and Gram-negative bacteria;

[0017] 4) Treatment with nano-GeO2 / CTAB composite can effectively reduce the cellulase activity of fungi;

[0018] 5) Nano-GeO2 / CTAB composite can effectively inhibit and kill fungal spores, preventing microbial damage to paper cellulose. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : Transmission electron microscope photo of the nano-GeO2 / CTAB composite prepared in Example 1; wherein, Figure 1 a is a morphological photograph of the nano-GeO2 / CTAB composite magnified 1000 times; Figure 1 b is a morphological photograph of the nano-GeO2 / CTAB composite magnified 8000 times;

[0020] Figure 2: Element distribution diagram of the nano-GeO2 / CTAB composite prepared in Example 1 (the inset is a diagram showing the percentage of each element); the abscissa is energy and the ordinate is intensity;

[0021] Figure 3 : The characterization result diagram of the nano-GeO2 / CTAB composite prepared in Example 1; wherein, Figure 3 a is the FTIR spectrum of nano-GeO2 / CTAB composite, the three lines in the figure are: CTAB (upper), Nano-GeO2 / CTAB (middle), Raw GeO2 (lower); the horizontal axis is the wavelength, and the vertical axis is the transmittance; Figure 3 b is the XRD diffraction spectrum of nano-GeO2 / CTAB composite, the two lines in the figure are: Nano-GeO2 / CTAB (upper), Raw GeO2 (lower); the horizontal axis is the scanning degree, and the vertical axis is the intensity; Figure 3 c is the ZETA potential curve of nano-GeO2 / CTAB composite; the horizontal axis is the scanning degree, and the vertical axis is the intensity; Figure 3 d is a bar graph of the transmittance of nano-GeO2 / CTAB complex; the abscissa is the concentration of nano-GeO2 / CTAB complex, and the ordinate is the transmittance;

[0022] Figure 4 : The inhibitory effect of the nano-GeO2 / CTAB complex prepared in Example 2 on Gram-positive bacteria and Gram-negative bacteria; wherein, Figure 4 a is the growth curve of the antibacterial treatment of Gram-negative bacteria (E. coli) with nano-GeO2 / CTAB complexes at concentrations of 0 μg / mL, 10 μg / mL, 20 μg / mL, 30 μg / mL, and 40 μg / mL for 30 minutes; the abscissa is time, and the ordinate is the absorbance value at 600 nm; Figure 4 b is the growth curve of the Gram-positive bacteria (S. aureus) treated with nano-GeO2 / CTAB complexes at concentrations of 0 μg / mL, 20 μg / mL, 40 μg / mL, 60 μg / mL, and 80 μg / mL after 30 minutes of antibacterial treatment; the abscissa is time, and the ordinate is the absorbance value at 600 nm; Figure 4 c are scanning electron microscope images of E.coli and S.aureus after being treated with nano-GeO2 / CTAB composite for 30 min;

[0023] Figure 5 : Bar graph showing the effect of the treatment of the nano-GeO2 / CTAB composite prepared in Example 2 on the cellulase activity of Fusarium, Aspergillus and Penicillium citrinum;

[0024] Figure 6: The effect of different concentrations of nano-GeO2 / CTAB complex treatment on the biomass of Fusarium, Aspergillus and Penicillium citrinum prepared in Example 2 is shown in the bar graph; wherein, Figure 6 b is a bar graph showing the effect of different concentrations of nano-GeO2 / CTAB complex treatment on Fusarium biomass; Figure 6 b is a bar graph showing the effect of different concentrations of nano-GeO2 / CTAB complex treatment on Aspergillus biomass; Figure 6 c is a bar graph showing the effect of different concentrations of nano-GeO2 / CTAB complex treatment on the biomass of Penicillium citrinum;

[0025] Figure 7 : The effect of the nano-GeO2 / CTAB composite treatment prepared in Example 2 on the germination rate and spore morphology of Fusarium, Aspergillus and Penicillium citrinum; wherein, Figure 7 a is the SEM image of the spore morphology of Fusarium, Aspergillus and Penicillium citrinum after being treated with nano-GeO2 / CTAB composite for 60 min; Figure 7 b is a bar graph showing the effect of nano-GeO2 / CTAB composite treatment on the germination rate of Fusarium spores at 0 min, 10 min, 20 min, 30 min, and 60 min; Figure 7 c is a bar graph showing the effect of nano-GeO2 / CTAB composite treatment on the germination rate of Aspergillus spores at 0 min, 10 min, 20 min, 30 min, and 60 min; Figure 7 d is a bar graph showing the effect of nano-GeO2 / CTAB composite treatment on the germination rate of Penicillium citrinum spores for 0 min, 10 min, 20 min, 30 min, and 60 min;

[0026] Figure 8 : SEM image of the inhibitory effect of the nano-GeO2 / CTAB composite prepared in Example 2 on microorganisms (bacteria, fungi); the abscissa is three fungi and bacteria (Fusarium, Aspergillus, Penicillium citrinum and Pseudomonas) isolated from aged paper, and the ordinate is different antibacterial treatment methods. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0028] Example 1

[0029] First, Raw GeO2 and NaOH were added into 10 mL of ultrapure water to make the concentration of Raw GeO2 in the mixed solution 0.9 M and the concentration of NaOH 0.2 M, and stirred at 25°C for 10 h; then 12 mL of 0.3 M CTAB solution was poured into the mixed solution and stirred for 6 h; after stirring, the Raw GeO2 mixture was heated at 100°C for 56 h; the product was washed with ultrapure water and anhydrous ethanol for 3 times respectively to remove the impurities that were not completely reacted from the product; finally, the product was dried in vacuum at 25°C to obtain a nano-GeO2 / CTAB composite with a mass of 1.2 g.

[0030] Next, the nano-GeO2 / CTAB composite prepared in Example 1 was characterized:

[0031] (1) The nano-GeO2 / CTAB composite was dropped onto a copper grid and dried overnight. After it was completely dried, the morphology of the nano-GeO2 / CTAB composite was observed using a transmission electron microscope.

[0032] like Figure 1 a and Figure 1 As shown in b, the TEM spectrum of the nano-GeO2 / CTAB composite shows that its overall appearance is a spindle-shaped structure composed of nano-GeO2 / CTAB composite filaments, while the purchased ordinary Raw GeO2 presents an irregular block structure, indicating that the addition of surfactant CTAB can play a good role in regulating the morphology of nano-GeO2 and successfully synthesize the nano-GeO2 / CTAB composite.

[0033] (2) The EDS spectrum sample preparation method is as follows: a 2 mg / mL nano-GeO2 / CTAB complex solution is prepared with ultrapure water, dropped on a clean silicon wafer and dried overnight. After it is completely dried, it is detected using a JSM-6010LA scanning electron microscope (CITACHI, Japan).

[0034] like Figure 2As shown in the illustration, the proportions of each element are: C element accounts for 35.52%, N element accounts for 5.86%, O element accounts for 23.83%, Ge element accounts for 23.01%, and Br accounts for 14.73% by mass; N and Br, as elements that make up CTAB, do not exist in Raw GeO2. The presence of N and Br can be detected in the EDS energy spectrum, indicating that CTAB is successfully modified around Raw GeO2 and the nano-GeO2 / CTAB complex is successfully synthesized.

[0035] (3) Figure 3 As shown in a, the FTIR spectra of Raw GeO2 and nano-GeO2 / CTAB composite were detected by SMHADZU 3346 using potassium bromide tablet method. The experimental results show that the nano-GeO2 / CTAB composite and Raw GeO2 have a strong affinity at 2020 cm -1 、872cm -1 There is an absorption peak near 1627cm, which may be caused by the asymmetric stretching vibration of Ge-O-Ge. CTAB and nano-GeO2 / CTAB composites have an absorption peak at 1627cm -1 The absorption peaks near this point are caused by -NH vibration; CTAB and nano-GeO2 / CTAB composites have absorption peaks at 2851 cm -1 、1627cm -1 There is an absorption peak nearby, while Raw GeO2 has no absorption peak nearby, indicating that CTAB is successfully modified around the nano-GeO2 / CTAB composite.

[0036] like Figure 3 As shown in Figure 2b, Raw GeO2 has sharp peak structures at 20.5°, 26°, 36°, 38°, 39.5°, and 41.8°, corresponding to the (100), (101), (110), (102), (111), and (200) planes, respectively. The peak located at the (101) crystal plane has a very strong intensity and a relatively narrow half-peak width, indicating that Raw GeO2 has good crystallinity. In contrast, the nano-GeO2 / CTAB composite prepared with surfactants does not have any clear XRD peaks. This may be because the surfactant CTAB plays a key role in guiding the crystal growth of the nano-GeO2 / CTAB composite, resulting in a lack of order in its crystal structure.

[0037] like Figure 3As shown in Figure c, the Zeta potential measurement results show that Raw GeO2 is positively charged when pH < 4, and negatively charged when pH > 4, and has the best stability at pH = 2; while the synthesized nano-GeO2 / CTAB complex is positively charged in Tris-HCl buffer at pH = 2 to 10, and the potential value is greater than 30 when pH is less than 5, and the potential value is greater than 25 at pH = 5 to 10. The synthesized nano-GeO2 / CTAB complex has a strong positive charge in Tris-HCl buffer at pH = 2 to 10, which is conducive to the dispersion of the protection, and can ensure that the nano-GeO2 / CTAB complex protection solution is more evenly dispersed between the aged paper cellulose when used, which has a better reinforcement and antibacterial effect on the paper cellulose.

[0038] like Figure 3 As shown in Figure d, with the increase of the concentration of nano-GeO2 / CTAB complex, the light transmittance of the solution gradually decreases. When the concentration of nano-GeO2 / CTAB complex is 1 mg / mL, the average light shielding rate of nano-GeO2 / CTAB complex in the ultraviolet region (UV 200-400nm) is about 25.12%; when the concentration of nano-GeO2 / CTAB complex is 4 mg / mL, the average light shielding rate of nano-GeO2 / CTAB complex in the ultraviolet region (UV 200-400nm) is about 76.13%. The higher light shielding rate of nano-GeO2 / CTAB complex in the ultraviolet region can effectively prevent the accelerated damage of ultraviolet light to paper cellulose. The average light shielding rate of the nano-GeO2 / CTAB complex in the visible light region (VIS 390-780nm) is about 19.8%; when the concentration of the nano-GeO2 / CTAB complex is 2mg / mL, the average light shielding rate of the nano-GeO2 / CTAB in the visible light region (VIS 390-780nm) is about 58.08%.

[0039] Example 2

[0040] First, Raw GeO2 and NaOH were added into 10 mL of ultrapure water, so that the concentration of Raw GeO2 in the mixed solution was 0.9 M and the concentration of NaOH was 0.5 M, and stirred at 25°C for 12 h; then 12 mL of 0.2 M CTAB solution was poured into the mixed solution and stirred for 5 h; after stirring, the Raw GeO2 mixture was heated and grown at 100°C for 50 h; the product was washed three times with ultrapure water and anhydrous ethanol respectively to remove the impurities that were not completely reacted from the product; finally, the nano-GeO2 / CTAB composite was obtained by vacuum drying at 25°C, and the product mass was 1.0 g.

[0041] The inhibitory effect of the nano-GeO2 / CTAB composite prepared in Example 2 on Gram-negative bacteria (E. coli) and Gram-positive bacteria (S. aureus) was studied:

[0042] (1) After 12 h of culture, E. coli and S. aureus were centrifuged at 3000 g for 10 min to collect the precipitate and washed with sterile PBS. The obtained E. coli and S. aureus were diluted to 10 6 CFU / mL, then add 0μg / mL, 10μg / mL, 20μg / mL, 30μg / mL, 40μg / mL, 50μg / mL nano-GeO2 / CTAB complex to treat E.coli for 30min; and use 0μg / mL, 20μg / mL, 40μg / mL, 60μg / mL, 80μg / mL, 100μg / mL nano-GeO2 to treat S.aureus for 30min. After the inhibition is completed, inoculate it into 50mL LB liquid culture medium at a ratio of one thousandth, and culture at 37℃, 180rpm shaking, and take 1mL of bacterial solution every 3h to detect OD 600 nm The absorbance value at .

[0043] The antibacterial growth curves of nano-GeO2 / CTAB composites against Gram-positive bacteria (S. aureus) and Gram-negative bacteria (E. coli) were studied. Figure 4 a and Figure 4 b). The results showed that after E. coli was treated with 0μg / mL, 10μg / mL, 20μg / mL, 30μg / mL, and 40μg / mL nano-GeO2 / CTAB complex for 30 minutes, the bacterial concentration increased with the increase of the concentration of nano-GeO2 / CTAB complex. 600nm It takes longer for the absorbance to reach 2.0. S. aureus also shows a similar phenomenon after being treated with different concentrations of nano-GeO2 / CTAB complex. When the concentration of nano-GeO2 / CTAB complex multifunctional protective solution is greater than 40μg / mL, the Gram-negative bacteria E. coli are completely killed and no longer grow within 30h. However, the Gram-positive bacteria S. aureus, after being treated with 40μg / mL for 30min, has a low OD value after 18h of culture. 600 nmThe absorbance value at the position reached 2; when the concentration of the nano-GeO2 / CTAB complex solution was greater than 80 μg / mL, the Gram-positive bacteria S. aureus was completely killed and no longer grew within 30 hours; the above experimental results confirmed that compared with S. aureus, the nano-GeO2 / CTAB complex had a stronger inhibitory effect on E. coli, which may be due to the different cell wall structures of Gram-positive bacteria and Gram-negative bacteria. The cell wall of Gram-negative bacteria is thinner than that of Gram-positive bacteria and is more easily destroyed by the nano-GeO2 / CTAB complex, resulting in Gram-negative bacteria being more easily killed.

[0044] (2) Scanning electron microscopy was used to observe the membrane damage morphology of the target bacteria after antibacterial treatment with nano-GeO2 / CTAB composites ( Figure 4 c). Obviously, the blank control sample (Control, using sterile PBS solution) showed a normal appearance, however, after adding the nano-GeO2 / CTAB composite, the bacterial membrane was observed to be destroyed ( Figure 4 c). The experimental results show that the nano-GeO2 / CTAB complex has a significant destructive effect on the cell membranes of E. coli and S. aureus. However, compared with E. coli, the cell membrane of S. aureus has relatively good integrity after the antibacterial treatment of the nano-GeO2 / CTAB complex, and there is no obvious large-area cell membrane collapse. It is confirmed that the nano-GeO2 / CTAB complex has a stronger destructive effect on the cell membrane of Gram-negative bacteria E. coli.

[0045] Example 3

[0046] The effect of the treatment of the nano-GeO2 / CTAB composite prepared in Example 2 on the cellulase activity of Fusarium, Aspergillus and Penicillium citrinum was studied:

[0047] Cellulase activity was determined using a cellulose (CL) activity detection kit (Solarbio). Figure 5As shown in the figure, the effect of 60min treatment of nano-GeO2 / CTAB complex on the cellulase activity of Fusarium, Aspergillus and Penicilliumcitrinum was studied. The experimental results showed that the cellulase activity of the three fungi Fusarium, Aspergillus and Penicillium citrinum was significantly reduced after treatment with nano-GeO2 / CTAB complex (P<0.01), which indicates that the treatment of nano-GeO2 / CTAB complex can effectively kill fungal cells and reduce the activity of cellulase in their cells. This result helps to reduce the destructive effect of cellulase secreted by fungi on paper cellulose. The blank control group sample (Control) used sterile PBS solution.

[0048] Example 4

[0049] The effects of the treatment with the nano-GeO2 / CTAB complex prepared in Example 2 on the biomass, spore germination rate and spore morphology of Fusarium, Aspergillus and Penicillium citrinum were studied:

[0050] (1) 10 mL of sterile water containing 0.05% Tween-20 was added to the PDA solid medium of Fusarium, Aspergillus, and Penicillium citrinum cultured for 3 days, and spores were scraped and collected using a disposable coating stick, and then washed three times. The collected spores of the three fungi were diluted to 10 6 CFU / mL, and then treated with 0mg / mL, 0.5mg / mL, 1mg / mL, 2mg / mL, and 4mg / mL nano-GeO2 / CTAB complex for 60min. After the antibacterial effect was over, it was inoculated into 50mL modified Martin liquid medium at a ratio of one thousandth, and cultured at 37℃, 180rpm for 5d. After the culture was over, the fungal organisms were filtered out, dried at 60℃, and weighed.

[0051] The experimental results showed that after being treated with 0mg / mL, 0.5mg / mL, 1mg / mL, 2mg / mL, and 4mg / mL of nano-GeO2 / CTAB complex for 60 minutes and cultured under suitable conditions for 5 days, the biomass of the three fungi Fusarium, Aspergillus, and Penicillium citrinum decreased with the increase of the concentration of nano-GeO2 / CTAB complex ( Figure 6 a. Figure 6 b and Figure 6c). After being treated with 4 mg / mL nano-GeO2 / CTAB complex for 60 minutes and cultured for 5 days under suitable conditions, no fungal spores germinated and the fungal biomass was 0, indicating that 4 mg / mL nano-GeO2 / CTAB complex can completely kill the three fungal spores of Fusarium, Aspergillus and Penicillium citrinum. Fusarium, Aspergillus and Penicillium citrinum treated with 1 mg / mL nano-GeO2 / CTAB complex were significantly different from the control group.

[0052] (2) 10 mL of sterile water containing 0.05% Tween-20 was added to the PDA solid medium of Fusarium, Aspergillus, and Penicillium citrinum cultured for 3 days, and spores were scraped and collected using a disposable coating stick, and then washed three times. The collected spores of the three fungi were diluted to 10 6 CFU / mL, and then treated with 1mg / mL nano-GeO2 / CTAB complex for 0min, 10min, 20min, 30min, and 60min respectively. After the inhibition was completed, the culture was carried out in the modified Martin liquid medium for 12h, and the spore morphology was observed under an optical inverted microscope. The spore bud length was greater than the spore diameter and was recorded as germination. The morphology before and after treatment with GeO2 / CTAB complex was observed using SEM.

[0053] The experimental results showed that with the extension of the treatment time of nano-GeO2 / CTAB complex, the spore germination rates of Fusarium, Aspergillus and Penicillium citrinum showed a downward trend. After 60 minutes of treatment with nano-GeO2 / CTAB complex, the spore germination rates of Fusarium, Aspergillus and Penicillium citrinum were only 8.33%, 2.66% and 9.33%, respectively, which were significantly different from the blank control group (P<0.01)( Figure 7 b. Figure 7 c and Figure 7 d). The spore morphology of Fusarium, Aspergillus and Penicillium citrinum after being treated with nano-GeO2 / CTAB composite for 60 min was observed by scanning electron microscopy ( Figure 7a). The experimental results show that the surface of the fungal spores of Fusarium, Aspergillus and Penicillium citrinum in the blank control group (Control) without treatment of nano-GeO2 / CTAB complex is relatively smooth and plump. After treatment with nano-GeO2 / CTAB complex, the cell membrane of some fungal spores is ruptured, and the surface of most fungal spores is relatively rough and flat, the cell morphology becomes irregular, and the cell wall invagination or protrusion increases significantly. This may be caused by the rupture of the spore cell membrane and the loss of water after treatment with nano-GeO2 / CTAB complex.

[0054] Example 5

[0055] The resistance of paper treated with the nano-GeO2 / CTAB composite prepared in Example 2 to infection by three fungi and one bacteria isolated from paper was studied:

[0056] Example 2 Experimental method for the resistance of the prepared nano-GeO2 / CTAB complex to fungal and bacterial infection: First, soak sterile 1*1cm filter paper in sterile PBS (Control), 1mg / mL Raw GeO2, and 1mg / mL nano-GeO2 / CTAB complex for standby use. After the fungi and bacteria separated from the paper are cultured on a modified Martin agar medium for 12 hours, the fungi and bacteria are dissolved in sterile PBS with an inoculation loop to form a bacterial solution. Take 20μL of the bacterial solution and spread it on a modified Martin agar medium, then cover the sterile filter paper soaked in the nano-GeO2 / CTAB complex on the surface of the culture medium. Invert and culture at 30°C for 3 days, and observe the inhibitory effect of the record protection solution on the fungi and bacteria isolated from the paper. Figure 8 As shown, the experimental results show that Raw GeO2 has no inhibitory effect on bacteria and fungi, while the nano-GeO2 / CTAB composite prepared by the present invention has a more significant inhibitory effect on three fungi (Penicillium citrinum, Aspergillus, Fusarium) and bacteria (Pseudomonas) isolated from paper.

Claims

1. A paper protection liquid based on nano-GeO2 / CTAB composite, which is prepared by the following steps: (1) First, raw GeO2 and NaOH are added to 10 mL of ultrapure water, so that the concentration of raw GeO2 in the mixed solution is 0.9 M and the concentration of NaOH is 0.2-0.5 M, and the mixture is stirred at 25-30° C. for 10-15 h; then 12 mL of CTAB solution with a concentration of 0.1-0.5 M is poured into the mixed solution, and the mixture is stirred for 5-8 h; after the stirring, the raw GeO2 mixture is heated at 90-110° C. for 48-72 h; after the reaction is completed, the reaction product is centrifuged at 8000-12000×g for 10-15 min and the reaction product is collected, and the reaction product is washed with ultrapure water and anhydrous ethanol for 2-4 times, respectively, to remove the impurities that have not reacted completely from the product; finally, the mixture is dried in vacuum at 50-60° C. to obtain the nano-GeO2 / CTAB composite; (2) Preparation of nano-GeO2 / CTAB complex protective solution: The nano-GeO2 / CTAB complex obtained in step (1) is dissolved in deionized water to obtain a nano-GeO2 / CTAB complex protective solution with a concentration of 0.1 to 5 mg / mL.

2. The paper protection liquid based on nano-GeO2 / CTAB composite according to claim 1, characterized in that: In step (1), the concentration of NaOH is 0.3-0.5M, the stirring time of the mixed solution of Raw GeO2 and NaOH at 25-30°C is 12-15h, the concentration of CTAB solution is 0.3-0.5M, the stirring time after adding CTAB solution to the mixed solution of Raw GeO2 and NaOH is 6-8h, the Raw GeO2 mixture is heated and grown at 90-110°C for 56-72h, and the impurities that have not reacted completely are removed from the product by washing with ultrapure water and anhydrous ethanol for 2-4 times respectively, which is first washing with ultrapure water for 2-4 times and then washing with anhydrous ethanol for 2-4 times.

3. The paper protection liquid based on nano-GeO2 / CTAB composite according to claim 1, characterized in that: In step (2), a nano-GeO2 / CTAB composite protective solution with a concentration of 1 to 5 mg / mL is obtained.

4. Use of the paper protection liquid based on nano-GeO2 / CTAB composite as claimed in any one of claims 1 to 3 in paper protection.

5. The use of a paper protection liquid based on a nano-GeO2 / CTAB composite in paper protection as claimed in claim 4, characterized in that: The method is to immerse the paper in a nano-GeO2 / CTAB composite protective solution at 10-40°C for 5-30 minutes, take it out, and then dry it at 20-40°C for 2-5 days.

6. The use of a paper protection liquid based on a nano-GeO2 / CTAB composite in paper protection as claimed in claim 5, characterized in that: The paper is immersed in a nano-GeO2 / CTAB composite protective liquid at 25 to 35°C for 5 to 10 minutes and then taken out; the drying temperature after the paper is taken out is 30 to 40°C, and the drying time is 2 to 3 days.

7. The use of a paper protection liquid based on a nano-GeO2 / CTAB composite in paper protection as claimed in claim 4, characterized in that: The invention relates to an application of a nano-GeO2 / CTAB composite protective liquid for reinforcing, inhibiting bacteria or isolating ultraviolet radiation from paper cellulose.

8. The use of a paper protection liquid based on a nano-GeO2 / CTAB composite in paper protection as claimed in claim 7, characterized in that: It is used to inhibit Staphylococcus aureus, Escherichia coli, Aspergillus niger, Penicillium, Trichoderma or Fusarium in paper.